Web-Based Outsourcing Workforce Information System : (Case Study PT. TRIMEGAH CIPTA MANDIRI) - Nur Hidayatus Shofyan; Dendy Kurniawan; Iman Saufik Suasana (Lembaga Pengembangan Kinerja Dosen, 2023)
Trimegah Cipta Mandiri is a company that operates in the service sector, namely outsourcing or what is known as outsourcing and this company, so far, for marketing still uses telephone, print media and comes directly to the prospective employment company so it cannot find out information about PT. Trimegah Cipta Mandiri is complete and up to date and takes quite a long time and costs quite a lot. Apart from that, when work relations require new potential workers, they experience difficulties, because they do not know directly the data about potential new workers. The purpose of writing this thesis is to design a web-based ordering system at PT. Trimegah Cipta Mandiri, so that it can act as a liaison between PT. Trimegah Cipta Mandiri and work relations without being limited by the location of a region and access times, as well as ease of obtaining information about prospective workers. new work required by work relations. The research methods used included field studies and literature studies. Field studies include interviews and direct observations. Meanwhile, literature research is carried out by looking for materials that are relevant to the problem. Design methods include system analysis in the form of Flow of Documents, system design in the form of Context Diagrams, DFD, ERD, Normalization. The results of the design are applied in the form of web design using the PHP programming language and database management using MySQL. After the system analysis and design has been carried out, it can be seen that PT. Trimegah Cipta Mandiri requires a more effective and efficient method of processing and data collection, so that it is hoped that it will be able to produce information quickly, precisely and accurately which is useful for improving services to work relations.